Exposure to Floods, Climate Change, and Poverty in Vietnam - Bangalore, Mook; Smith, Andrew; Veldkamp, Ted (World Bank, Washington, DC, 2016)
With 70 percent of its population living in coastal areas and low-lying deltas, Vietnam is exposed to many natural hazards, including river and coastal flooding. These hazards are expected to worsen due to climate change, and the impacts of any change in hazard magnitude may be particularly acute in this region. This paper examines the exposure of the population and poor people in particular to current and future flooding at the country level, using new high-resolution flood hazard maps and spatial socioeconomic data. The paper also examines flood exposure and poverty at the local level within Ho Chi Minh City. The national-level analysis finds that a third (33 percent) of today’s population is already exposed to a flood, which occurs once every 25 years, assuming no protection. For the same return period flood under current socioeconomic conditions, climate change may increase the number exposed to 38 to 46 percent of the population. Climate change impacts can make frequent events as important as rare ones in terms of exposure: for instance, the estimates suggest a 25-year flood under future conditions can expose more people than a 200-year flood under current conditions. Although poor districts are not found to be more exposed to floods at the national level, the city-level analysis of Ho Chi Minh City provides evidence that slum areas are more exposed than other parts of the city. The results of this paper show the benefits of investing today in flood risk management, and can provide guidance as to where future investments may be targeted. Furthermore, while the main strategy in Vietnam today to manage flood risk is to reduce exposure, the increase in exposure estimated in this paper provides support that alternative strategies to reduce vulnerability (such as financing for floor-raising) or improve the ability-to-adapt of households (such as social safety nets) may warrant increased attention.